Case report: a heterozygous loss-of-function variant of the ERG gene in a family with vascular pathologies - Erhart, Philipp; Dikow, Nicola; Schwaibold, Eva; Dihlmann, Susanne; Grond-Ginsbach, Caspar; Körfer, Daniel; Schaaf, Christian P.; Oeser, Sabrina; Hinderhofer, Katrin; Böckler, Dittmar; Zerella, Jiarna R.; Scott, Hamish S.; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe transcription factor ERG (erythroblast transformation-specific-related gene) has been identified as a key regulator of vascular function by suppressing inflammation in endothelial cells (ECs). Dysregulation of ERG due to genetic risk variants is linked to chronic inflammation in conditions such as atherosclerosis and aortic aneurysms.Case presentationThis research work investigates the role of the ERG gene in the development of a systemic arterial aneurysm manifestation. Given the previous implication of ERG in vascular development, we now report a loss-of-function variant (Leu212*) in the ERG gene, segregating in a family with vascular pathologies. Multiple arterial aneurysms were observed in one family member, and early onset of vascular-associated stroke in another individual carrying the familial ERG variant. Histological analysis of arterial aneurysm specimen showed comparable expression of ERG in endothelial cells of the vasa vasorum in samples from the patient and controls.ConclusionOur report discusses the possibility that loss-of-function variants in ERG may act as a risk factor for arterial disease.
Gesehen am 12.01.2026